THE ROLE OF PUBLIC RELATIONS OF THE MINISTRY OF RELIGIOUS AFFAIRS OF TEBING TINGGI CITY IN IMPROVING PUBLIC SATISFACTION WITH PUBLIC SERVICES - Khadizah Rania Cahyani Damanik; Muhammad Husni Ritonga (Program Pascasarjana UIN Sumatera Utara, 2026)
This study examines the role of Public Relations at the Ministry of Religious Affairs Office of Tebing Tinggi City in improving public satisfaction with public services. The study focuses on how public relations functions as a communication bridge, information provider, institutional image builder, and supporter of transparency in religious public services, particularly marriage administration, hajj services, and religious education. This research employed a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews with public relations officers, institutional leaders, and service users, supported by field observations and institutional documentation. The data were analysed through data reduction, data display, and conclusion drawing. The findings show that public relations has contributed to improving service accessibility through digital information management, social media use, the Integrated One-Stop Service system, and the SILATU platform. These efforts help simplify procedures, strengthen public trust, and reduce information gaps between the institution and society. However, the effectiveness of public relations remains constrained by limited human resources, budget limitations, inadequate digital infrastructure, and low public digital literacy. The study concludes that strengthening public relations requires more adaptive communication strategies, continuous public education, improved staff capacity, and stronger institutional support. These elements are essential to creating public services that are transparent, responsive, inclusive, and oriented toward public satisfaction.